2020
DOI: 10.1186/s12889-019-8006-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cervical cancer screening among migrants and non-migrants in Germany: results from a large-scale population survey

Abstract: Background: Studies from European and non-European countries have shown that migrants utilize cervical cancer screening less often than non-migrants. Findings from Germany are inconsistent. This can be explained by several limitations of existing investigations, comprising residual confounding and data which is restricted to only some regions of the country. Using data from a large-scale and nationwide population survey and applying the Andersen Model of Health Services Use as the theoretical framework, the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
5
25
1
Order By: Relevance
“…Similar to research from other countries, [3][4][5][6] this study shows that migrant women residing in Austria are less likely to receive annual Pap smears than non-migrant women. These disparities are independent of a different distribution of demographic and other confounding factors between the population groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to research from other countries, [3][4][5][6] this study shows that migrant women residing in Austria are less likely to receive annual Pap smears than non-migrant women. These disparities are independent of a different distribution of demographic and other confounding factors between the population groups.…”
Section: Discussionsupporting
confidence: 83%
“…A study from Germany based on the Gesundheit in Deutschland aktuell survey showed that non-European Union (EU) and EU migrant women were at 33% (adjusted odds ratio (aOR) ¼ 0.67, 95% confidence interval (95% CI) ¼ 0.55-0.81) and 20% (aOR ¼ 0.80, 95% CI ¼ 0.66-0.97), respectively, lower odds of Pap smear testing in the 12 months before the survey than the female majority population. 5 Similar results were reported from a register-based study. 6 However, conversely, an analysis of routine data in Germany reported higher odds of utilization (aOR ¼ 1.11; 95% CI ¼ 1.08-1.14).…”
Section: Introductionsupporting
confidence: 83%
“…Our study revealed differences in the screening uptake amongst migrant-origin women, consistent with previous studies [10][11][12][13][22][23][24][25][26]30,46,64]. Our study is the first population register-based study to report participation in the Finnish mass screening program among these specific migrant-origin groups compared with the general Finnish population in Finland to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…Migrant populations have increased globally, including in Finland [14,15], and the health status of these population groups has become a public health concern, highlighting the need to strengthen healthcare systems [16][17][18][19]. Studies have revealed the underutilization of cervical cancer screening services among some migrant-origin groups compared with host populations [10][11][12][13][20][21][22][23][24][25][26]. Consequently, persisting health inequities will increase national healthcare expenditure [27].…”
Section: Introductionmentioning
confidence: 99%
“…These features might influence their access and utilization of healthcare services [ 28 ], such as CCS. There seem to be disparities in CCS and a lower likelihood of screening participation among several migrant origins, even in some countries with screening opportunities [ 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Both a higher incidence and risk of CC have been revealed among some migrant populations compared with the host population [ 22 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%